Contrasting Mechanical and Hydraulic Properties of Wet and Dry Fault Zones in a Proposed Shale‐Hosted Nuclear Waste Repository - Luis Felipe Orellana; Carolina Giorgetti; Marie Violay (Geophysical Research Letters)
Abstract The underground disposal of high‐level nuclear waste is a pressing issue for several countries. In Switzerland, the Opalinus Clay formation is a shale with favorable barrier properties. However, small‐to‐large faults intersecting the formation bring the long‐term integrity of the future repositories into question. Here we present the first systematic laboratory study on the frictional strength, stability, dilatancy, and permeability of simulated Opalinus Clay gouge under typical repository conditions. Wet gouges exhibit an extremely low coefficient of friction (μf~0.16), velocity‐strengthening behavior, and shear‐enhanced dilatancy at the onset of slip, and permeability increase. Conversely, dry gouges remain weak (μf~0.36) but exhibit a transition from unstable to stable sliding with increasing sliding velocity. Thus, we infer that faults hosted in Opalinus Clay could be easily reactivated via aseismic creep, possibly acting as poor fluid conduits. However, if temporarily dried, the faults become potentially unstable, at least, at low sliding velocities (<~10 μm/s).